What is 6y 3y 2 3y 2

Understand math 5, textbook

193 9.2 LINEAR SYSTEMS OF EQUATION IN TWO VARIABLES EXERCISES 9.24 Solve the system of equations graphically and mathematically! Note the different solution cases and do the test! a) {x - y = 0 2x + y = 3 c) {5x + y = –2 –10x - 2y = 4 e) {- x = 2 2x + 6y = 5 b) {x - 4y = –1 - 2x + 3y = - 3 d) {- x + 2y = 9 3x - 6y = –16 f) {- 2x - 2y = –6 y = 3 - x 9.25 solve with the elimination method! Note the different solution cases and do the test! a) {3x - 6y = 2 2x - 4y = 1 c) {2x - 3y = 8 - 3x + 9 _ 2 y = -12 e) {2x - 1.2y = - 0.4 - x + 0.6y = 0.2 b) {3x + 2y - 14 = 0 - 2x + 5 _ 2 y - 6 = 0 d) {- 2x + 10y = 11 4x + 5y = 8 f) {3x - 4.5y - 1 = 0 - 2x + 3y - 6 = 0 9.26 Solve with the substitution method or the comparison method and do the test! How many solutions are there? a) {3x - 2y = 0 - 6x + 4y = 2 c) {x - y - 3 = 0 - 2x + 2y = - 6 e) {x + y = 4 2x - y = 5 b) {3x + 2y = 0 5x + y = 2 d) {x + 7y = 9 7x + 13y = - 9 f) {2x = - 0.4 5x + 0.7y = –0.3 9.27 Solve the following system of equations! How many solutions does it have? a) {x - 2.4y = -1.4 3x - 0.7y = 2.3 b) {x - 2.4y + 3.4 = 0 3x - 0.7y + 3.7 = 0 c) { x - 1.2y - 2.6 = 0 0.5x - 0.6y = 1.3 9.28 Does the following system of equations have no, exactly one or an infinite number of solutions? a) {2 (x - 3y) + 4 (x + 2y) = 3 (x - 5y) + 45 - 4 (x + y) + 3 (2x - y) = 5 (x + y) - 42 c) {-11x + 5 (2x - 2y) - 4 (x - y) = 3 4 (2x + 3y) - 3 (x + 2y) = -3 b) {x + y + 6 (x + y) = 3 (x + y) + 86 2 (x + y) - 18 (x + 2y) = 9 (3x + y) - 369 d) {2 (x - 2y) + 3 (y - 2x) = 2x + y - 7 3 (x + y) - 2 (x - y) = 4 (2x + 3y) - 105 9.29 Solve and do the test! a) {4x - 3y - 2 _ 4 = 14 2x + 5 _ 11 - y _ 2 = 2 c) {4x - 2y - 1 _ 6 = 14 8x + 5 _ 2 - y _ 3 = 2 e) {2y - 3 _ 2 = 1 6x - 5 _ 10 - y _ 2 = 1 _ 4 b) {3x - 3y + 1 _ 4 = 2 2x + 1 - 3y _ 6 = 4 _ 3 d) {- x - 3 _ 7 - 3y = 0 6x + 5 _ 23 - y _ 2 = 1 f) {2x + 7y _ 3 = 1 3 _ 2 x + 21 _ 4 y = 9 _ 4 9.30 solve and do the test! a) {2 2 x + 1 _ 3 - y - 1 _ 4 3 = 6 2 x - 1 _ 3 + y + 1 _ 4 3 4 2 x - 2 _ 3 + y - 2 _ 4 + 1 3 = 2 2 x - 1 _ 2 + y + 1 _ 2 3 b) {x _ 2 - 2 2 x + 2 _ 3 - y + 5 _ 5 3 = x + 10 _ 10 - y - 8 _ 2 x _ 10 + y _ 5 - y _ 2 = x _ 2 - 2 2 x - 1 _ 3 + 1 _ 2 3 R Ó learning applet ka6s2e Only {for testing purposes - property 4 4 of the V rlags öbv

Made with FlippingBook

RkJQdWJsaXNoZXIy ODE3MDE =